High School Physics Student Worksheets Assisted by Augmented Reality: Enhancing Problem Solving Skills - Denny, Dwinanda Permata Sari; Muliyati, Dewi; Bakri, Fauzi (Current STEAM and Education Research, 2023)
Practicum is a component of physics learning which is important in increasing the literacy of students in high school. This article describes the results of research and development of students physics worksheets with problem-solving stages equipped with AR (Augmented Reality) media. The research method used is a research and development method with the Dick and Carey approach. The resulting Physics Student worksheet is presented with stages to train students' problem solving skills. Activity components in Student Worksheet: short theory, videos with the help of AR (Augmented Reality) technology, practicum data, tables, graphs, graphic interpretation, analysis of practicum concepts for each topic presented in the practicum. The stages of problem solving in Student Worksheet: (a) describe an initial problem and a brief theory; (b) ask questions related to the problems given earlier; (c) describes the analysis of practicum data, and (d) explains the analysis of the physics concept of the practicum results. The results of this study have been validated by Student Worksheet media experts, physics concept material experts, and learning experts. To fulfill all aspects, it can be shown that a proper Student Worksheet is used to train the problem solving skills of high school students.